Censorship: X, Instagram, Facebook, YouTube and TikTok (Turkey) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in Turkey. Data sourced from CensoredPlanet.
Censorship Incident ID: TR-2024-0003. Severity: warning. Confidence: 75%